1966
DOI: 10.1042/bj0980669
|View full text |Cite
|
Sign up to set email alerts
|

The dietary-regulated biosynthesis of high-sulphur wool proteins

Abstract: 1. When the diet of sheep is supplemented by the abomasal infusion of sulphur-containing amino acids or casein, a special group of proteins, with a very high content of sulphur (about 8.3%), is incorporated into the high-sulphur proteins of wool. These special proteins cannot be detected in control wool from the same sheep. 2. This is a naturally occurring process, as these special proteins are found in wool from sheep on a high level of nutrition under ordinary conditions of feeding, and in wool of an inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 4 publications
3
55
0
Order By: Relevance
“…The wool components are not present in equal proportions and this is especially true of component 5. It has been found that the Dorset Horn wool high-sulphur and low-sulphur proteins have electrophoretic patterns indistinguishable from those previously obtained for Merino wool (O'Donnell and Thompson 1964;Gillespie and Reis 1966;Fraser et al 1972;Crewther et al 1976). It was also found, in agreement with earlier observations (Gillespie 1968(Gillespie , 1972, that the constituent protein fractions are present in different relative proportions in these keratins-for example, the highsulphur protein content of wool, horn, and hoof is 29, 11 and 11 % respectively; the high-tyrosine protein content of wool, horn and hoofis 9, 13 and 10 % respectively.…”
Section: Low-sulphur Proteins (I) Compositionmentioning
confidence: 48%
See 3 more Smart Citations
“…The wool components are not present in equal proportions and this is especially true of component 5. It has been found that the Dorset Horn wool high-sulphur and low-sulphur proteins have electrophoretic patterns indistinguishable from those previously obtained for Merino wool (O'Donnell and Thompson 1964;Gillespie and Reis 1966;Fraser et al 1972;Crewther et al 1976). It was also found, in agreement with earlier observations (Gillespie 1968(Gillespie , 1972, that the constituent protein fractions are present in different relative proportions in these keratins-for example, the highsulphur protein content of wool, horn, and hoof is 29, 11 and 11 % respectively; the high-tyrosine protein content of wool, horn and hoofis 9, 13 and 10 % respectively.…”
Section: Low-sulphur Proteins (I) Compositionmentioning
confidence: 48%
“…The reasonably high sulphur content of the wool (3·75 %) indicates the presence of ultra-high-sulphur proteins (Gillespie and Reis 1966), and the presence of these proteins was confirmed by an electrophoretic run at pH 11 (Fig. 1, indicated by arrow).…”
Section: High-sulphur Proteins (I) Compositionmentioning
confidence: 98%
See 2 more Smart Citations
“…The outstanding role of sulphur in keratin chemistry and biosynthesis (cf. Gillespie and Reis 1966) Arginine 22·0 29·3 23·0 26·2 11·16 2·1 17·6 24·7 Aspartic acid 7·51 40·1 7·65 34·8 8·26 6·5 1·6 3·05 Threonine 3·61 19·3 3·47 15·8 4·09 3·2 7·2 4·69 Serine 5·47 29·2 4·57 20·8 11·66 9·1 9·7 9·98 Glutamic acid 12·22 65·2 14·28 65·0 4·90 3·8 8·1 2·30 Proline 2·53 13·5 1·41 6·41 6·73 5·3 8·0 5·96 Glycine 3·10 16·6 2·08 9·48 7 ·15 5·6 5·8 12·8 Alanine 4·30 22·9 4·01 18·3 2·89 2·3 2·8 2·98 Val...…”
Section: Discussionmentioning
confidence: 99%